ORGANIZATION OF WORK WITH EDUCATIONAL TEXT IN THE PROCESS OF HUMANITARIAN TRAINING OF FUTURE PHILOLOGISTS ON THE BASIS OF COMPETENCE APPROACH - Мішеніна, Т. М. (Pedagogy of Higher and Secondary Education, 2011)
The article explains the system will work with academic texts in the training of future humanitarian philologists on the basis of competence-based approach. Disclosed information aktivizatorskaya and motivational functions of academic teats; described forms of implementing the educational text.